ANALISIS KEPEMIMPINAN, LINGKUNGAN KERJA, BUDAYA ORGANISASI DAN KOMITMEN SEBAGAI PENENTU KINERJA ORGANISASI IPNU JAWA BARAT - Sapari, Riza Paisal; Badruzaman, Jajang; Hanapia, Asep Yusuf (Jurnal Ekonomi Manajemen, 2024)
The West Java Nahdlatul Ulama Student Association (IPNU) faces various challenges in optimizing organizational performance. This is reflected in the failure to achieve targets on several performance indicators, such as the implementation of Aswaja strengthening activities, instructor delegation, and the implementation of the SMAS application which did not go according to plan. Additionally, ineffective leadership causes overlap in organizational activities. A disorganized work environment, weak organizational culture, and low management commitment to organizational responsibilities also become obstacles in achieving optimal performance. This research analyzes the influence of leadership, work environment, organizational culture, and commitment on the organizational performance of IPNU West Java using census methods and path analysis. The results show that simultaneously, the four variables have a significant effect on organizational performance. Partially, leadership has a positive but not significant effect, while work environment, organizational culture and commitment have a positive and significant effect.